A REVIEW OF OPTICALLY PUMPED FAR-INFRARED LASER LINES FROM METHANOL ISOTOPES - Pereira, D.; Moraes, João Carlos Silos [UNESP]; Telles, E. M.; Scalabrin, A.; Strumia, F.; Moretti, A.; Carelli, G.; Massa, C. A. (Plenum Publ Corp, 1994)
The technique of optical pumping in polar molecules is the most efficient for Far-Infrared (FIR) laser generation, providing also a versatile and powerful tool for molecular spectroscopy in this spectral region. Methanol (CH3OH) and its isotopic varieties are the best media for optically pumped FIR laser, with over thousand lines observed, and the most widely used for investigations and applications. In this sense, it is important organize and make available catalogues of FIR laser lines as complete as possible. Since the last critical reviews of 1984 [1] on methanol and its isotopic varieties [2,3,4], over hundred papers have been published dealing with hundreds of new FIR laser lines. In 1992 a review of FIR laser lines from CH3OH was presented [5]. In this communication we extend this work to the other methanol isotopes, namely CH3OD, CD3OH, CD3OD, (CH3OH)-C-13, (CD3OH)-C-13, (CD3OD)-C-13, (CH3OH)-O-18, CH2DOH, CHD2OH and CH2DOD.
Keywords: FIR LASER LINES; METHANOLS ISOTOPES